(untitled) (Economic and Political Thought, 2016)
The starting point for the analysis is the relationship between geopolitics and globalization, which seem to be crucial in explaining the contemporary international reality. Great superpowers, which are the pillars of globalization processes, promote their values, but at the same time miss no opportunity and do not lose their willpower to enter new domains of influence, often at the expense of their partners or contractors. A major change in understanding world geopolitics lies in the fact that the centre of gravity of power is shifting from the West to the East and South. Simultaneously, a “great reconvergence” of the East and the West is underway, involving efforts to create a counterweight to the U.S. by such powers as China or Russia. All this means that the post-Cold War international order is still in transition, and it is marked by polycentrism and interpolarity, and even a decline of polarity understood traditionally. With regard to the scale of power, there is a hierarchical and heterarchical diversity of participants, while the principles that govern the functioning of the international system as a whole are coordination and its derivatives – superordination and subordination.